Efek Mediasi Penggunaan Financial Technology pada Pengaruh Literasi Keuangan terhadap Kinerja Keuangan UMKM Kabupaten Gresik - Anugraini, Mardiyah; Khusnah, Hidayatul; Muttaqiin, Ninnasi (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
This study aims to analyze the mediation effect of the use of financial technology (fintech) on the influence of financial literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Gresik Regency. Financial literacy is one of the important factors that influences the ability to manage MSME finances. However, along with the development of financial technology, fintech is expected to play a role as a mediator in strengthening the influence of financial literacy on financial performance. The data used in this study are primary data obtained from distributing questionnaires that meet the research criteria. The method used in sampling is purposive sampling. The sample consists of 100 MSME actors in Gresik Regency. The research method used is a quantitative approach with data collection through a survey of MSMEs in Gresik Regency. Data were analyzed using a structural model (SEM-PLS) to test the relationship between financial literacy, the use of fintech, and MSME financial performance. The results of this study indicate that financial literacy has a positive effect on financial performance. Furthermore, financial literacy has a positive effect on Financial Technology. Financial Technology is able to mediate the influence of financial literacy on financial performance.